Pulsed electrophoretic membrane cleaning for dead-end ultrafiltration process - Abdul Latif Ahmad,; Norliza Ibrahim, (2002)
Membrane separation technology has been identified as a new and clean technology and as an alternative to the conventional separation technology since it can offer some advantages over those separation technologies. Nevertheless, membrane fouling appears to be the major bottleneck of this technology. Many approaches have been proposed to reduce membrane fouling. The approach considered in this paper is the application of electric pulse to remove deposits from the membrane surface. An experimental test rig is constructed to study the effect of electric pulse on the membrane cleaning effectiveness. The filter cake is collected after every application of each electric pulse to ensure that the deposited materials which has been removed from the membrane surface after each electric pulse will not be redeposited onto the membrane surface. The dead-end ultrafiltration of silica dioxide (Si02) dispersion is conducted with various values of pulse interval, pulse duration and feed concentration. It is found that the application of the electric pulse to reduce membrane fouling and restore high permeation rate is effective in the dead-end filtration process. The application of electric pulses across the membrane gives a higher permeation rate than the conventional ultrafiltration process